Integrons and integron-related antibiotic resistance in acinetobacter - Thomas, Robin (Division of Medical Microbiology, 2017)
Acinetobacter baumannii is responsible for an increasing number of nosocomial infections in patients receiving intensive care and comprehensive antibiotic resistance of these organisms hampers treatment of infections due to A.baumannii. The molecular basis of antibiotic resistance in A.baumannii has not been extensively investigated. A few studies have demonstrated the role of plasmids and transposons in resistance in this organism, but there is little data on the role of integrons and integron-associated antibiotic resistance. This study was undertaken to determine the incidence of integrons in clinical isolates of Acinetobacter from Groote Schuur Hospital (GSH), Cape Town and Universitas Hospital (UH), Bloemfontein, and to characterise the resistance genes carried in the variable regions of these integrons.